COLLABORATION OF PARENTS AND TEACHERS IN ESTABLISHING STUDENTS' PRAISE CHARACTER IN THE COVID-19 PANDEMIC - Mutik Nur Fadhilah; Mohamad Nurahman (JIP Jurnal Ilmiah PGMI, 2021)
The purpose of this study was to determine the collaboration program of parents and teachers in establishing commendable morals and the implications of the collaboration program of parents and teachers in establishing commendable morals. The research method which was used was descriptive qualitative research. The research was conducted at SD (Elementary School) Anak Saleh Malang City. The results showed that the collaboration of parents and teachers in establishing commendable morals are; the collaboration program which consisted of four activities, namely: parenting, an association where, during the pandemic, the interaction process was through WhatsApp groups; morning activity, an early morning activity to start the learning process; home visit, visiting students' homes and meets parents to exchange opinions; self-development project consisting of 15 extracurricular activities. In every program, there was a process of moral formation, especially in spiritual, responsibility, discipline, sportsmanship, creativity, and love for the homeland, gratitude and sincerity in doing. The implications of the collaboration program in establishing commendable morals are in three research subjects, namely: teachers understand the culture of each student and provide the best formulation in the learning process better; parents get a new discourse in educating children and become partners of teachers in providing examples; students get a balance in the hereafter and worldly in the process of forming commendable morals.